PENGARUH PROSES CARBONITRIDING TERHADAP MATERIAL DASAR BEARING SUJ2 - Sumiyanto, Sumiyanto; Abdunnaser, Abdunnaser (Bina Teknika, 2017)
Bearing is a prayer one part of the holding machine elements because Important role of bearing namely functions to review rivet a shaft so that the shaft can be spun without experiencing excessive friction. Bearing generally used to review round prop shaft where at occurred many friction. From then that on bearing component materials had made of strong enough for a review allows the shaft well as other machine elements working good and optimal. Research singer aims to review determine mechanical properties of components bearing material with carbon steel high (high carbon steel) SUJ 2 the treated Heat Carbonnitriding with Temperature of 850 ° C, Hardening 830 ° C with cooling oil during a 15 minute shower taxable income next using the water conditioning on hold for 15 minutes bath Tempering 185 ° C and cooled with room temperature for 120 minutes. Testing results chemical composition is known that the basic ingredients of the basic SUJ 2 has a Fe content of 98.23%, C 0.93% and 0.10% Cr content that can be classified as high carbon steel crhoom. Observations showed metaloggrafi the homogeneous microstructure with more Subtle form of austenite grains, martensite and carbides, carbide where the surface surrounding the bearing component. Results  hardnes test components vickers bearing SUJ 2 has a value to keep pace with the heat treatment of non-taxable income 199.8 HV experience heat treatment 1 process being 910 HV, on process heat treatment 2 being 810 HV.